Recollections of a conference interpreter: a brief encounter with the European Parliament: A BRIEF ENCOUNTER WITH THE EUROPEAN PARLIAMENT - A. G. Anacleto, Maria Helena (POLISSEMA – Revista de Letras do ISCAP, 2019)
Although I believe that a theoretical discussion on consecutive and simultaneous interpretation is as valuable as any academic problematical exchange of ideas can be, it is not the purpose of this article. I agree that it is necessary to reach a definition of consecutive and simultaneous interpretation if we are to understand the language used in this essay. By “consecutive”, it is indisputably accepted by the majority of theorists that we understand that there is a speaker who delivers a speech during, let us set as an example, three to ten minutes, and immediately after an interruption, the interpreter will render the same speech in the target language; in “simultaneous interpretation”, there are two speakers: speaker one is delivering a speech which is only understandable to another speaker – the interpreter – who is addressing a much wider audience by means of a microphone in a booth and headphones worn by the listeners of speaker one. It is more frequent in simultaneous than in consecutive interpretation that the interpreter is a native speaker of the target language.